Pengaruh Solvabilitas Terhadap Return Saham Dengan Earning Per Share Sebagai Variabel Moderasi - Adinda Novia Ardianti; Elva Nuraina; Liana Vivin Wihartanti (JAMER : Jurnal Akuntansi Merdeka, 2020)
Abstract— The purpose of this study is to analyze the effect of solvency on stock returns by using EPS as a moderating variable in the Food and Beverage companies listed on the IDX for the period 2015-2017. This study uses a type of quantitative research with a sampling technique that is purposive sampling. The research observation data were 36 companies. The analysis technique uses descriptive statistical analysis, classic assumption test and hypothesis testing using Moderated Regression Analysis (MRA). The results of the study prove that solvency has a not significant positive effect on stock returns and EPS reinforces the effect of solvency on stock returns. The smaller the level of solvability, the smaller the risk obtained. Keywords—: Solvability; Returns; EPS.